Grammar of the shot - Bowen, Christopher J. (Routledge, 2023)
The new edition of Grammar of the Shot teaches readers theoretical principles behind successful visual communication in motion media through discussions of shot composition, depth cues, lens choices, lighting, screen direction, and more. Designed as an easy-to-use reference, this book is a staple of any filmmaker's library.